The evolution of Palaeolake Flixton and the environmental context of Star Carr, NE. Yorkshire: stratigraphy and sedimentology of the Last Glacial-Interglacial Transition (LGIT) lacustrine sequences. Issue 1 (February 2015) - Palmer, A.P.; Matthews, I.P.; Candy, I.; Blockley, S.P.E.; MacLeod, A.; Darvill, C.M.; Milner, N.; Conneller, C.; Taylor, B.
Abstract The basal topography and sediments recording the Last Glacial-Interglacial Transition (LGIT) from Palaeolake Flixton, North Yorkshire have been reinvestigated by a detailed auger and borehole survey. The data presented here, from the area to the north of Flixton Island and the River Hertford, suggests the basal topography of Palaeolake Flixton is irregular with deep and areally small basins interspersed within a gravel surface ca. 21 m OD. At its shallowest the gravel surface is ca. 2 m below current land surface and the deeper, steep-sided basins are up to 9 m in depth. Examination of the sediment sequences indicates the deeper basins accumulate sediments from the Dimlington Stadial (DS), Windermere Interstadial (WI), Loch Lomond Stadial (LLS) and the Holocene, whilst the shallower sequences only record the Holocene. The configuration of the deposits in the basins suggest that lake levels declined during the WI from 24 to 23 m OD and then fell further during the LLS to ca. 20.90 m OD. The lake water levels then rose slowly during the Holocene to a height of between 23 and 24 m OD. These fluctuations in lake water level at the transition from the LLS to Holocene perhaps indicate that the configuration of the water body during the resettlement of the area in the Mesolithic was different to previous reconstructions, with lower water levels and a greater area of land exposed for habitation. This highlights the potential for additional preservation of archaeological assemblages in the area of the former lake. Moreover the complex basal stratigraphy suggests that a systematic analyses of the Palaeolake Flixton sedimentary archive is required to resolve high-resolution palaeoclimate data from this lake sequence.